(untitled) (PANGEEA, 2025)
The work refers to the need to create a topographical support, which will support the topographic-cadastral works necessary for the materialization in the field of the intravillage limit of an Administrative-Territorial Unit (UAT), in order to modify and update its general urban plan (PUG). In the case of the commune of Saschiz (UAT Saschiz), this topographical support was materialized in the field through a geodetic network of densification, which would ensure both the implementation of the land works necessary for the materialization and determination of the intra-village limit of the component villages of the commune (Saschiz, Cloasterf and Mihai Viteazu) as well as the subsequent performance of various topo-cadastral works intended for the sustainable development and urban development of the respective administrative territory, such as: sewerage expansion; cadastre works, modernization of street infrastructure, etc.